COMPARATIVE ANALYSIS OF PYTHAGOREAN PROBLEMS IN INDONESIAN AND SINGAPOREAN MATHEMATICS TEXTBOOKS: AN OVERVIEW OF COGNITIVE LEVEL, REPRESENTATION FORM, CONTEXTUAL FEATURE, AND RESPONSE TYPE - Lestiana, Herani Tri; Maula, Lifa Muflikhatul; Winarso, Widodo (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Several studies revealed that mathematics problems in textbooks, which were expected to encourage students’ reasoning and problem-solving skills, were still lacking. This study aimed to compare Pythagorean problems in Indonesian and Singaporean mathematics textbooks based on the cognitive level of Bloom's taxonomy, representation form, contextual feature, and response type. The data were collected through documentation and observation. The research results indicated that on the cognitive level, the C3-C4 level dominated the Pythagorean problems in Indonesian and Singaporean textbooks. Regarding representation form, Pythagorean problems in Indonesian textbooks used visual and combined forms, while Singaporean textbooks applied mostly combined forms. In contextual feature and response type, Pythagorean problems in Indonesian and Singaporean textbooks used non-application and closed-ended problems. Therefore, the result of this study is expected to contribute to the improvement of high-quality mathematics textbooks, which can compete internationally to support students’ learning. Abstract: Beberapa penelitian menunjukkan soal-soal matematika dalam buku ajar Indonesia yang diharapkan dapat mendorong kemampuan penalaran dan pemecahan masalah siswa masih kurang. Penelitian ini bertujuan untuk membandingkan soal-soal Teorema Pythagoras dalam buku matematika Indonesia dan Singapura berdasarkan tingkat kognitif Bloom, bentuk representasi, fitur kontekstual, dan tipe respon. Pengumpulan data dilakukan melalui dokumentasi dan observasi. Hasil penelitian menunjukkan bahwa pada tingkat kognitif, soal Pythagoras dalam buku teks Indonesia dan Singapura sebagian besar berada pada kategori C3-C4. Terkait bentuk representasi, soal-soal Pythagoras dalam buku Indonesia lebih banyak menggunakan bentuk visual dan gabungan, sedangkan buku Singapura lebih banyak menggunakan bentuk gabungan. Pada aspek fitur kontekstual dan tipe respon, soal-soal Pythagoras baik dalam buku Indonesia dan buku Singapura menggunakan soal non-aplikasi dan soal tertutup. Oleh kare itu, hasil penelitian ini diharapkan dapat berkontribusi pada peningkatan kualitas buku teks matematika yang dapat bersaing secara internasional, untuk mendukung pembelajaran siswa.